Reading sentences in spanish: some similarities and differences between children with dyslexia and those with deafness - Alegria, Jesus; Carrillo , Maria-Soledad; Rueda, Mercedes I.; Domínguez Gutiérrez, Ana Belén (Anales de Psicología / Annals of Psychology, 2020)
The present study compares the strategies to read sentences used by Spanish-speaking children with dyslexia (n = 107) and cochlear-implanted children with deafness (n = 61). The results show that children with deafness, but not with dyslexia, adopt the key-word-strategy (KWS), which consists of identifying some content words of the sentence while ignoring the function words. Furthermore, it appeared that the KWS was associated with poor syntactic ability. Moreover, when Dyslexic and Deaf Groups were carefully matched at reading level with normally developing children (Control Group, n = 785) all of the differences between dyslexics and normally developing children disappeared. Children with hearing loss however were still poor at dealing with function words and consequently maintained their tendency to use the KWS. These results exclude the hypothesis that the KWS is a broadly used procedure to compensate for reading deficits but seems, rather, to depend on poor syntactic ability.